? carbonic anhydrase is required for female fertility in Drosophila melanogaster. - Syrjänen, L.; Valanne, S.; Kuuslahti, M.; Tuomela, T.; Sriram, A.; Sanz, A.; Jacobs, H.T.; Rämet, M.; Parkkila, S. (Frontiers in Zoology, 2015)
Carbonic anhydrases (CAs, EC 4.2.1.1) are ubiquitous enzymes that catalyze the reversible hydration reaction of carbon dioxide. CAs are present as six structurally divergent enzyme families: ?, ?, ?, ?, ? and ?. ?-CAs have a wide distribution across different species including invertebrates. Previously, we showed that Drosophila melanogaster ?-CA is a highly active mitochondrial enzyme. In this study, we investigated the function of Drosophila ?-CA by silencing the expression of the ?-CA gene using UAS/GAL4-based RNA interference (RNAi) in Drosophila in vivo. Crossing ?-CA RNAi lines over ubiquitous Actin driver flies did not produce any viable progeny, indicating that ?-CA expression is required for fly development. RNAi silencing of ?-CA ubiquitously in adult flies did not affect their survival rate or function of mitochondrial electron transport chain. Importantly, ?-CA RNAi led to impaired reproduction. All ?-CA knockdown females were sterile, and produced few or no eggs. Whole ovaries of knockdown females looked normal but upon cadherin staining, there was an apparent functional defect in migration of border cells, which are considered essential for normal fertilization. These results indicate that although Drosophila ?-CA is dispensable for survival of adult flies, it is essential for female fertility.